if alpha and beta are zeroes of a polynomial f(x)=xsquare -p(x+2)-cthen find the value of (alpha+2) (beta+2)

Asked by nayan kumar | 23rd Jun, 2013, 11:17: AM

Expert Answer:

f(x) = x2 -px - 2p - c
Sum of roots = alpha + beta = p
Product of roots = (alpha) (beta) = -(2p+c)
 
Now, we have:
(alpha+2) (beta+2) = (alpha) (beta) + 2 alpha + 2 beta + 4 = -(2p +c) + 2p + 4 = 4 - c

Answered by  | 23rd Jun, 2013, 11:48: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.